Brookings Papers on Economic Activity 1 : 1993 - Edited by William C.Brainard and George L. Perry (Washington, D.C Brookings Institution, 1994)
Issues consist of papers from conferences held at the Institution.
Include Graph and Tables
Keywords: United States -- Economic history -- Economics